THE ROLE OF MADRASAS IN THE SOCIAL LIFE OF THE EMIRATE OF BUKHARA IN THE LATE 19TH – EARLY 20TH CENTURIES - Elmurodova Nigora (Modern American Journals, 2025)
This article examines the role of madrasas in the social life of the Emirate of Bukhara. The study analyzes their influence on education, religious and spiritual development, legal and administrative structures, as well as cultural life. Particular attention is given to their economic foundations, financial support through waqf revenues, and their functions within the judiciary and state administration. The article also highlights the scientific and educational significance of Bukhara’s madrasas in the late 19th and early 20th centuries, the internal conflicts among scholars, and their impact on society. Thus, it is argued that madrasas in the Emirate of Bukhara were not only centers of religious and scholarly education but also important institutions of broader social and cultural life.
Keywords: Madrasahs, Education, Waqf, Bukhara emirate, Socio-cultural life, Mudarris, Student, Islam, Religious sciences.